Pre-Participation Cardiovascular Screening in Competitive Athletes: An Evidence-Based Review of Strategies and Risk Stratification - Wasilewski , Luiza; Koladzyn, John; Słodyczka, Anna; Jankowski , Gabriela; Margielewska, Weronika; Jankowski, Marianna; Badran, Mahmoud; Twombly, Gregory; Siemaszko, Kai (Journal of Education, Health and Sport, 2026)
Background: Competitive athletes are exposed to sustained physiological stress that may reveal previously unrecognized structural or electrical cardiac disease, thereby predisposing susceptible individuals to exercise-related sudden cardiac events. Pre-participation cardiovascular screening has become an established component of athlete care. Aim: To review the rationale, components, strengths, and limitations of contemporary cardiovascular screening strategies in competitive athletes and to examine current controversies and future directions. Material and methods: A narrative review of PubMed-indexed literature published between 2017 and 2025 was conducted, focusing on guideline statements, systematic reviews, and cohort studies addressing cardiovascular screening in athletes. Summary: The reviewed literature indicates that structured screening based on history, physical examination, electrocardiography, and selective imaging facilitates early identification of occult cardiac disease and supports informed eligibility and management decisions. Variability in diagnostic performance, inconsistency in ECG interpretation, and differences in screening approaches remain areas of ongoing debate. Conclusions: Cardiovascular screening in competitive athletes functions as a structured strategy for risk mitigation that supports early detection and informed clinical decisions. Its effectiveness depends on appropriate expertise, consistent implementation, and access to follow-up pathways. Continued refinement of screening criteria and implementation models is needed to optimize athlete safety while preserving participation.